Moth pheromone receptors: gene sequences, function, and evolution - Zhang, Dan-Dan; Löfstedt, Christer (Frontiers in Ecology and Evolution, 2015)
The detection of female-released species-specific sex pheromones in moths is mediated by the pheromone receptors that are expressed in the sensory neurons in the olfactory sensilla of conspecific male antennae. Since the pioneering studies on the tobacco budworm Heliothis virescens and the silkworm Bombyx mori a decade ago, genes encoding pheromone receptors have been identified from a number of moth species. Pheromone receptor genes constitute a specialized olfactory receptor subfamily that shares sequence homology. In most cases the pheromone receptor genes are more abundantly expressed in male antennae, and the expression is confined to the neurons in the long sensilla trichodea, which are responsible for pheromone sensing. Both highly specific and more broadly tuned pheromone receptors have been described in various moth species. We review the advances in moth pheromone receptor studies over the past decade, including the methods used in receptor gene isolation and functional characterization, the different ligand profiles of the identified receptors, and the evolution of this multigene family.